Impact of intracavity power variations toward ultrashort pulse generation - Abas, Ahmad Fauzi; Lau, Kuen Yao; Al-Moliki, Yahya Mohammed; Aladadi, Yosef Taher; Alresheedi, Mohammed Thamer; Mahdi, Mohd Adzir (MDPI, 2023)
This study demonstrates a passive mode-locked erbium-doped fiber laser with a graphene nanoplatelet-saturable absorber (GNP-SA) that generates ultrashort pulses within femtosecond pulse duration. The GNP-SA is fabricated via a direct transfer approach by mechanically exfoliated graphene on a fiber ferrule. Its characteristics include 0.8% modulation depth, 8.7 MW/cm2 saturation fluence, and 36.8% absorbance. The quality of ultrashort pulses is studied with a variation of intracavity circulating powers that is controlled through an optical coupler. By changing the light intensity in the cavity, the optical amplification property in the erbium-doped fiber is also impacted. The increment of the output coupling ratio increases the population inversion in the active gain medium, which leads to the change of lasing wavelength from 1558 to 1532 nm. Using a 50% output coupling ratio, the fiber laser generates 960 fs pulse duration, 11.08 MHz repetition rate, and 6.05 mW output power. This study contributes to the understanding of oscillating light behavior while changing its intracavity power that affects the optical amplification properties.